PERENCANAAN JADWAL INDUK PRODUKSI DENGAN MENGGUNAKAN LINIER PROGRAMMING PADA INDUSTRI MANUFAKTUR PT â€Xâ€ - Nurcahyo, Yusuf Eko (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2015)
The fluctuated demand is one of constrain in planning and scheduling process because it affects the cost of production and inventory costs incurred. PT